Aiken Index Analysis to Determine The Contents Validity of Project Assessment Instrument in Learning Islamic Religion and Character in the Independent Curriculum - Wahyuni, Vera (Jurnal Sustainable, 2023)
This research aims to analyze the validity of the content of the project assessment instrument for Islamic religious learning and character in the independent curriculum based on the Aiken validity index so that the instrument can measure what it will measure. The research method used is a quantitative descriptive method based on content validity results which are calculated using the Aiken V formula. Content validity data was obtained from 5 experts, namely 2 Islamic religious education experts and 3 evaluation experts. The content validity test in this study used 4 assessment criteria, namely Very Appropriate (VA), Appropriate (A), Not Appropriate (NA), Very Inappropriate (VI). The Project Assessment instrument for learning Islamic religious education and morals resulted in 15 indicators being declared valid with an average Aiken index above 0.873. The project assessment is declared to be suitable for measuring what it wants to measure, and can be used to measure the results of Islamic religious education and character learning project assignments in the independent curriculum.